PERSEPSI SISWA TERHADAP PENGGUNAAN CHAT GPT SEBAGAI BELAJAR DI ERA DIGITAL - Asisah, Nur Asisah; Latifah, St. Latifah Raihani; haliq, Abdul haliq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of artificial intelligence (AI), particularly ChatGPT, has brought significant changes to the world of education. This research aims to analyze the influence of ChatGPT usage on the critical thinking skills of vocational high school students, identify patterns of ChatGPT utilization in the learning process, and explore the challenges faced in its use. The research employs a qualitative approach with in-depth interview methods involving 5 students who actively use ChatGPT in their learning activities. Data was collected through interviews and analysis of students' conversations with ChatGPT to obtain a comprehensive picture of their experiences. The results show that students utilize ChatGPT primarily to obtain references, overcome creative blocks, and expedite task completion. Although ChatGPT helps in terms of efficiency, there are concerns about dependency that may hinder the development of independent analysis and evaluation abilities. This research concludes that the influence of ChatGPT on critical thinking skills has a dualistic nature - on one hand, it can enhance analytical abilities through personalized learning, but on the other hand, it has the potential to reduce students' cognitive efforts if used without clear limitations.